THE IMPORTANCE OF INTERNATIONAL ASSESSMENT PROGRAM - PISA AND PIRLS IN TEACHING MODERN PHYSICS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article provides information about modern educational programs PISA and PIRLS, and outlines the directions of international educational programs.